Serviço de atendimento móvel de urgência (SAMU) e a assistência às urgências psiquiátricas - Bonfada, Diego (2010)
The objective of this work which is characterized as an applied research, with a qualitative exploratory approach and has case study character has been the analysis of the conceptions and dealings of health professionals of SAMU in Natal RN about the attendance of psychiatric urgencies. The information was collected between the months of March and April of 2010, by means of semi-structured interviews, performed with 24 health professionals integrating of SAMU-Natal as well as the usage of direct observation technique, performed in the institution's medical regulation room. Both the number of professionals involved in the interviews and the bringing about of the observations, were determined by saturation methods in qualitative research's information collecting. The interviews and observations were transcribed and submitted to contents analysis technique , more specifically, to thematic analysis, which made possible to reach the deepest levels, that go beyond what has simply been manifest in the speech of the interviewed, getting to the relations among the categories and social structures of the issue of the research. Keeping this in mind, three analysis categories have been built, namely: conceptions and concepts of psychiatric urgencies shared by health professionals in SAMU-Natal; attendances to psychiatric urgencies in SAMU-Natal; and the Brazilian Psychiatric Reformation under the view of the SAMU-Natal's health professionals. Reflection about the analyzed information revealed discussions pertaining to the stigma and prejudice on mental illness, and also, pointed out to some hindrances which impair the attendance to individuals in mental suffering in SAMU-Natal. The interviewed health professionals' conceptions on the individual in psychical crisis involve concepts of unpredictability, aggressiveness and risk, stigmatizing elements and historically associated to the social hazard ideology and need for mentally sicks' segregation. The predominance of these conceptions, seen in health professionals speech, had identifiable reflexes on assistance to psychiatric demands performed by SAMU-Natal, namely: indiscriminate request for military police's presence during psychic crisis intervention, neglect about occasions that involve mental health patients, as well as repetitive assisting practice directed on physical contention, and transportation to psychiatric hospital. Associated to it, the professionals have shown distorted and reductionist understanding about Brazilian Psychiatric Reformation, and, in the majority, haven't lent credibility to present model of attention to mental health, based on psycho-social treatment, pointing their speech to a need for psychiatric patient's internment. In this sense, we notice that the hospital-centered and excluding model conceived by classical psychiatry still remains alive in these health professionals' mentality as a reference to psychiatric urgency's assistance. Therefore, the research revealed a sequence of elements, that make us think about the challenges that health sector and society must face to realize Brazilian Psychiatric Reformation's principles and guidelines